Pellet moulding machine design and simulation analysis of the effect of angle variation in the mold hole on pellet alloy pressure - Husni Husni; Arif Faturrahman; Muhammad Rizal (Politeknik Negeri Lhokseumawe, 2023)
The development of aquaculture in Indonesia has increased every year. However, in reality, farmers find failed fish harvests arising from fish feed problems. Various problems in the field occurred by fish farming business actors due to the incompatibility of the pallet molding machines used with the quality of raw materials and the high price of fish feed. For this reason, it is necessary to have a new technology in the form of a pellet molding machine to overcome the problems that often occur. This study aims to design a pellet molding machine with modifications to the angle of the mold hole and analyze changes in pressure values and production rates from the effect of the angle given to the mold to obtain a good mix of pellets and a shorter production speed. The method used is design and simulation, with machine variables that have been designed using angles of 30º, 45º, and 60º. The highest pressure value data is obtained at an angle of 45º with a maximum pressure value of 11.86 Pa and the lowest pressure value is at an angle of 30º with a maximum pressure value of 10.62 Pa. The highest speed value is obtained at an angle of 45º and 60º with a value of 4 .8 m/s and the lowest value is obtained at an angle of 30 o with a value of 4.7 m/s. In a pellet molding machine that uses an unmodified mold, the maximum pressure value is 10.36 and the speed is 4.6 m/s, which means that the angle at the mold hole gives an increase in pressure and production speed which will make the pellets have better mix and faster production time.